2020
DOI: 10.3390/molecules25204838
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Differentially Regulates α7 and α4 Neuronal Nicotinic Acetylcholine Receptor Levels in Rat Hippocampal Neurons

Abstract: Neuronal α7 and α4β2 are the predominant nicotinic acetylcholine receptor (nAChR) subtypes found in the brain, particularly in the hippocampus. The effects of lovastatin, an inhibitor of cholesterol biosynthesis, on these two nAChRs endogenously expressed in rat hippocampal neuronal cells were evaluated in the 0.01–1 µM range. Chronic (14 days) lovastatin treatment augmented cell-surface levels of α7 and α4 nAChRs, as measured by fluorescence microscopy and radioactive ligand binding assays. This was accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…α7 nAChRs in cholesterol-rich liquid-ordered lipid domains (Brusés et al, 2001;Marchand et al, 2002;Oshikawa et al, 2003;Zhu et al, 2006), may constitute a non-activatable pool of nicotinic receptors, as suggested by Báez-Pagán and coworkers (Báez-Pagán et al, 2016). Long-term inhibition of cholesterol biosynthesis by the drug lovastatin differentially augments cell-surface levels of α4β2 and α7 nAChRs in neurites and soma of rat hippocampal neurons (Borroni et al, 2020). In conclusion, dysregulation of cholesterol homeostasis affects the stability, distribution and conductance of both muscle-type and neuronal nAChRs.…”
Section: Nachr and Cholesterolmentioning
confidence: 78%
See 1 more Smart Citation
“…α7 nAChRs in cholesterol-rich liquid-ordered lipid domains (Brusés et al, 2001;Marchand et al, 2002;Oshikawa et al, 2003;Zhu et al, 2006), may constitute a non-activatable pool of nicotinic receptors, as suggested by Báez-Pagán and coworkers (Báez-Pagán et al, 2016). Long-term inhibition of cholesterol biosynthesis by the drug lovastatin differentially augments cell-surface levels of α4β2 and α7 nAChRs in neurites and soma of rat hippocampal neurons (Borroni et al, 2020). In conclusion, dysregulation of cholesterol homeostasis affects the stability, distribution and conductance of both muscle-type and neuronal nAChRs.…”
Section: Nachr and Cholesterolmentioning
confidence: 78%
“…Brain cholinergic system dysfunction has also been reported in ASD (Hardan and Handen, 2002;Eissa et al, 2018). Since nAChR function is influenced by its lipid microenvironment (see reviews in Barrantes, 2004Barrantes, , 2017 and cell-surface trafficking of nAChRs is dependent on cholesterol metabolism (Pediconi et al, 2004;Borroni et al, 2020) we explore in this review the various neurological alterations described in ASD and their possible association with an abnormal crosstalk between nAChRs and cholesterol.…”
Section: Introductionmentioning
confidence: 98%
“…The α7 nAChR subtype of nAChRs is predominantly located in cholesterol-rich Lo domains [117][118][119][120]. Other studies from our laboratory indicate that longterm inhibition of cholesterol biosynthesis can differentially augment cell-surface levels of both α4β2 and α7 nAChRs in neurites and soma of rat hippocampal neurons [121].…”
Section: Nachrmentioning
confidence: 99%
“…Changes in cholesterol levels alter the translational mobility of the receptor in the plane of the plasma membrane, as measured by fluorescence recovery after photobleaching and fluorescence correlation spectroscopy [ 165 ] and single-molecule localization microscopy [ 166 , 167 ]. Cell-surface trafficking of nAChRs is dependent on cholesterol metabolism [ 168 , 169 ]. Pharmacological long-term inhibition of cholesterol biosynthesis by the statin lovastatin differentially augments cell-surface levels of α4β2 and α7 nAChRs in neurites and soma of rat hippocampal neurons [ 169 ].…”
Section: Importance Of Lipids In Dendritic Spine Compartmentalizationmentioning
confidence: 99%
“…Cell-surface trafficking of nAChRs is dependent on cholesterol metabolism [ 168 , 169 ]. Pharmacological long-term inhibition of cholesterol biosynthesis by the statin lovastatin differentially augments cell-surface levels of α4β2 and α7 nAChRs in neurites and soma of rat hippocampal neurons [ 169 ]. Misbalances in brain cholesterol homeostasis affect cholinergic signaling involving α4β2 and α7 nAChRs and indirectly impact on the number and distribution of other neuroreceptors at dendritic spines, with important consequences for brain function.…”
Section: Importance Of Lipids In Dendritic Spine Compartmentalizationmentioning
confidence: 99%